Parallel Distractor Rejection as a Binding Mechanism in Search - Dent, Kevin; Allen, Harriet; Braithwaite, Jason; Humphreys, Glyn (Frontiers in Psychology, 2012)
The relatively common experimental visual search task of finding a red X amongst red O’s and green X’s (conjunction search) presents the visual system with a binding problem. Illusory conjunctions of features across objects must be avoided and only features present in the same object bound together. Correct binding into unique objects by the visual system may be promoted, and illusory conjunctions minimised, by inhibiting the locations of distractors possessing non-target features (e.g. Treisman & Sato, 1990). Such parallel rejection of interfering distractors leaves the target as the only item competing for selection; thus solving the binding problem. In the present article we explore the theoretical and empirical basis of this process of active distractor inhibition in search. Specific experiments that provide strong evidence for a process of active distractor inhibition in search are highlighted. In the final part of the article we consider how distractor inhibition, as defined here, may be realised at a neurophysiological level. Treisman, A, & Sato, S. (1990). Conjunction search revisited. Journal of Experimental Psychology: Human Perception and Performance, 16, 459-478.